Seeding new ventures: green thumbs and fertile fields ; individual and environmental drivers of informal investment - László Szerb; Siri Terjesen; Gábor Rappai (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This study explores individual and country-level environmental drivers of informal seed investment. We examine four types of informal investors based on business ownership experience (or no such experience) and close family relationship with investee (or no such relationship): classic love money, outsider, kin owner and classic business angel investors. At the environmental level, we are interested in the role of economic development, income tax policies, start-up costs, pro-enter-rise government programmes, availability of debt financing, entrepreneurship edu-cation and culture. Using Global Entrepreneurship Monitor data from telephone in-teriews with 257,793 individuals in 31 countries, including 5,960 informal investors, we report drivers for the four types of seed investment. Descriptive statistics are consistent with prior research: informal investors are likely to be older males who work full-time, earn high incomes, perceive start-up opportunities in the environ-ment, and believe that they have the skills to start their own businesses. At the environmental level, we find that countries with higher percentages of informal investors are significantly likely to have higher levels of economic development, higher business start-up costs, higher levels of entrepreneurship education, lower income taxes and lower power distance. Other environmental effects on the four populations of informal investors are reported and discussed, as well as implica-tions for practice, policy and future research.
Keywords: L26; E22; M13; N2; 330; informal investment; individual drivers; environmental drivers; entrepreneurial careers; business ownership; new venture financing; Investition; Unternehmensfinanzierung; Klein- und Mittelunternehmen; Unternehmensgründung; Wirtschaftswachstum; Befragung